Factors associated with agrobiodiversity conservation: A case study on conservation of rice varieties in Barak valley, Assam, India - Talukdar, Nazimur Rahman; Choudhury, Parthankar (Journal of Scientific Agriculture, 2017)
Agrobiodiversity contributes to food security, increase productivity, economic returns and provides social, cultural and ecological functions. The present study aims to investigate the factors associated with agrobiodiversity conservation, with respect to the rice varieties in the Barak valley of Assam, India. Barak valley has high ecological and genetic diversity, and is one of the important regions of NE India in terms of agricultural productivity. More than 80% of the people of the Valley depend upon agricultural activities for their livelihood. Fieldwork included semi-structured interviews, visit to crop field (inventory) and survey to households to register seed exchange network, socio-economic characteristics and other factors influencing agrobiodiversity conservation. We used correlation analysis to know the association of various factors. Thirty six rice varieties were found to be traditionally conserved. Indegee refers to the number informants inform someone’s name when asked about their shareholders. For example, one informant name was informed by five people when asked to list the name of seed givers or receivers, then the informant would have an indegree of five. It was found that Farmers who had higher indegree conserved more traditional varieties than those farmers who had less indegree. It can be hypothesized that conservation of traditional varieties is related with various co-relating factors. Our findings will surely contribute to the conservation of genetic resources. Establishment of seed bank and application of vermicompost technique are suggested to check genetic erosion and fulfill the inadequacy of organic fertilizers.